Attraversamenti di genere e risurrezioni del tragico: nuove considerazioni sul mito atridico in Virginia Woolf (Comparatismi, 2025)
Beginning with the reflections articulated in the dense essay On not Knowing Greek (1925), in which Virginia Woolf entrusts – primarily through the figure of Electra and her corporeality – her meditations on the tragic genre, the present article seeks to investigate the underlying reasons for Woolf’s progressive, and often implicit, engagement with the mythological material of the House of Atreus. The analysis will therefore consider how the foundational structure of Myth may be resemanticized through a process that foregrounds the role of literary genre, ultimately advancing an argument concerning the presence of a tragic modus within the novel Mrs Dalloway. In conclusion, the article will explore the ways in which Woolf’s proximity to Greek tragedies enables her prose to activate metaphors, motifs, and sensations drawn from a tragic background – one that is revitalized through a fundamental inquiry into the formal and aesthetic status of modernist novels.
Keywords: House of Atreus; Greek Tragedy; Modernist Novel; Enactment; Gender